1988
DOI: 10.1111/j.1432-1033.1988.tb14407.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of the allosteric AMP site of biodegradative threonine dehydratase of Escherichia coli with 8‐azido‐AMP

Abstract: The photoreactive AMP analog, g-azido-AMP, stimulated the activity of biodegradative threonine dehydratase of Escherichia coli in a reversible manner and, like AMP, decreased the K , for threonine. The concentrations required for half-maximal stimulation by AMP and 8-azido-AMP were 40 pM and 1.5 pM, respectively, and the maximum stimulation by 8-azido-AMP was 25% of that seen with AMP. Gel-filtration experiments revealed that 8-azido-AMP stabilized a dimeric form of the enzyme, whereas AMP promoted a tetrameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
8

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
20
0
8
Order By: Relevance
“…After centrifugation, the precipitate of cell debris was discarded and the supernatant was incubated with shaking with 150 mL of Ni/nitrilotriacetic acid agarose suspension (Qiagen) at room temperature for 1 h. The resin was washed stepwise with the same buffer, the ProTa derivative was eluted with a buffer containing 10 mm Tris/HCl (pH 6.3), 6 m urea, 0.5 m NaCl, 20% glycerol, 0.5 m imidazole and precipitated with three volumes of ethanol in the presence of 0.3 m sodium acetate (pH 5.0). The pellet was dissolved in water, and the 1 mg ProTa aliquot was subjected to radiolabelling by incubating with 100 mCi [g- 32 zz, zz-Rev, zz-NES, and zz-H1 were isolated from E. coli JM109 cells freshly transformed with pQEzz60, pQEzzRev, pQEzzNES, and pQEzzH1, respectively. For production of zz-Rev, zz-NES and zz-H1, cell cultures were grown at 30 8C in 10 mL of LB medium containing 0.2% glucose and 100 mg´mL 21 ampicillin, whereas`Super medium' (2.5% Bacto tryptone, 1.5% Bacto yeast extract, 0.5% NaCl) with the same additives was used for production of zz.…”
Section: Production and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…After centrifugation, the precipitate of cell debris was discarded and the supernatant was incubated with shaking with 150 mL of Ni/nitrilotriacetic acid agarose suspension (Qiagen) at room temperature for 1 h. The resin was washed stepwise with the same buffer, the ProTa derivative was eluted with a buffer containing 10 mm Tris/HCl (pH 6.3), 6 m urea, 0.5 m NaCl, 20% glycerol, 0.5 m imidazole and precipitated with three volumes of ethanol in the presence of 0.3 m sodium acetate (pH 5.0). The pellet was dissolved in water, and the 1 mg ProTa aliquot was subjected to radiolabelling by incubating with 100 mCi [g- 32 zz, zz-Rev, zz-NES, and zz-H1 were isolated from E. coli JM109 cells freshly transformed with pQEzz60, pQEzzRev, pQEzzNES, and pQEzzH1, respectively. For production of zz-Rev, zz-NES and zz-H1, cell cultures were grown at 30 8C in 10 mL of LB medium containing 0.2% glucose and 100 mg´mL 21 ampicillin, whereas`Super medium' (2.5% Bacto tryptone, 1.5% Bacto yeast extract, 0.5% NaCl) with the same additives was used for production of zz.…”
Section: Production and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…The localization of MTI-II, however, remains somewhat complicated. As described above, MTI-II contains a bipartite NLS and is actively translocated into the nuclei of undifferentiated cells (13,(15)(16)(17)(18), but it remains in the cytoplasm of differentiated and nonproliferated rat cells (13,15). Here, we wanted to identify the localization of MTI-II in glucocorticoid hormone-depleted cells and to determine whether MTI-II can colocalize with GR in the nucleus in the presence of hormone.…”
Section: Mti-ii Colocalizes With Gr In the Nucleus In The Presence Ofmentioning
confidence: 99%
“…Although the N-terminal region of MTI-II consists of 28 amino acids that are homologous to thymosin ␣1 (corresponding to 46% identity), the proposed role of this protein as the precursor of thymosin ␣1 has been brought into question, because MTI-II was found to have no coding sequence for signal peptides, as would be expected for a secretory protein, but instead was found to have an active bipartite nuclear localization signal (NLS) in its C-terminal region (15). Thus, this protein is actively translocated into the nuclei of Xenopus oocytes (16), HeLa S3 cells (17), dedifferentiated rat primary hepatocytes (13), COS cells (15), Reuber H35 rat hepatoma cells (15), and T24 (human bladder carcinoma) cells (18). Furthermore, MTI-II has been reported to bind to the linker histone H1 in vitro (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of zinc in catalysis, structure and regulation, has been demonstrated in many enzymes (Vallee and Galdes, 1984). Recently, it has been shown that in the case or a 1PkDa protein from rat liver, which inactivates rat liver 6-phosphofructokinase, carboxylate groups serve as an excellent ligand for zinc co-ordination (Brand et al, 1988). In addition, carboxylic acid residues have also been implicated in the catalytic activity of RNAase T1 (Takahashi and Moore, 1982) and Staphylococcal nuclease (Weber et al, 1991).…”
mentioning
confidence: 99%